Exercise-Induced Bronchoconstriction in Children - Klain, Angela; Indolfi, Cristiana; Dinardo, Giulio; Contieri, Marcella; Decimo, Fabio; Miraglia Del Giudice, Michele (Frontiers in Medicine, 2022)
Exercise-induced bronchoconstriction (EIB) is a transient airflow obstruction, typically 5 to 15 minutes after physical activity. The pathophysiology of EIB is related to the thermal and osmotic changes of the bronchial mucosa, which cause the release of mediators and the development of bronchoconstriction in the airways. EIB in children often causes an important limitation to physical activities and sports. However, by taking appropriate precautions and through adequate pharmacological control of the condition, routine exercise is extremely safe in children. This review aims to raise awareness of EIB by proposing an update, based on the latest studies, on pathological mechanisms, diagnosis, and therapeutic approaches in children